CREDCHEM-Project : developing and testing a credit-system enhancing the mobility in the chemical sector - Eberhardt, Christiane [Verfasser]; Luomi-Messerer, Karin [Verfasser] (My University, 2011)
This article describes the ECVET pilot project "CREDCHEM", which aims at implementing ECVET principles (i.e. formulation of learning outcomes, design of units, etc.) in the chemical sector. Besides this, CREDCHEM tests ECVET during mobility periods. "On the one hand, learners can complete training modules abroad, which will then be recognised for their formal training programme at home. On the other hand, partner countries develop specific training modules, which both (or even more) countries will recognise as additional qualifications." (Extract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.3.3.3 Mobilität; G 1.2.4.1.4 Verarbeitendes Gewerbe; I 2.2 Europa; Europäisches Leistungspunktesystem; Pilotprojekt; Berufsausbildung; Mobilitätsförderung; Auslandsaufenthalt; Chemische Industrie; Europa